Health Seeking Behaviour and Treatment Intentions of Dengue and Fever: A Household Survey of Children and Adults in Venezuela. - Jelte Elsinga; Erley F Lizarazo; Maria F Vincenti; Masja Schmidt; Zoraida I Velasco-Salas; Luzlexis Arias; Ajay Bailey; Adriana Tami (Public Library of Science (PLoS), 2015)
BACKGROUND:Dengue in Venezuela is a major public health problem with an increasing incidence of severe cases. Early diagnosis and timely treatment influences the outcome of dengue illness, as delay in care-seeking is significantly associated with complications leading to severe dengue. We aimed to understand patterns of health seeking behaviour (HSB) in individuals exposed to high dengue incidence in order to improve early attendance to health centres. METHODS:Between September 2013 and February 2014 a cross-sectional household survey was performed in Maracay, Venezuela. Intended HSB of adults and children's parents/guardians was assessed with respect to fever or suspected dengue. Data was collected through structured questionnaires from 105 individuals. RESULTS:Most individuals felt at risk of dengue and believed it could be a deadly disease. In the case of suspected dengue, the majority (60%) would choose to first seek medical help versus first treating at home, in contrast to 11% in the case of fever. Amongst those who decided to visit a doctor, a suspected dengue infection would prompt them to search medical help earlier than if having only fever (p<0.001). Multivariate analysis modelling showed that the independent factors associated with the intention to firstly visit a doctor versus treating at home in the case of dengue were feeling at risk (OR = 3.29; p = 0.042) and being an adult (as opposed to caring for a child as a parent/guardian; OR = 3.33, p = 0.021), while having had a previous dengue infection (OR = 0.29; p = 0.031) and living in the neighbourhood Caña de Azúcar (OR = 0.28, p = 0.038) were negatively associated with seeking medical care as their first action. CONCLUSION:Knowledge of HSB related to dengue is scarce in the Americas, our study attempts to contribute to a better understanding of HSB in this region. Improving early dengue disease recognition and awareness may enhance prompt attendance to medical care in affected populations and thereby reduce mortality and severity of dengue. Especially for those with a previous dengue infection, efforts have to be made to promote prompt health centre attendance.